Lower Urinary Tract Symptoms: Prevalence, Perceptions, and Healthcare-Seeking Behavior amongst Nigerian Men - Rufus Wale Ojewola; Ezekiel Sofela Oridota; Olanrewaju Samuel Balogun; Ezra Olatunde Ogundare; Taiwo Opeyemi Alabi (The World Journal of Men's Health, 2016)
Purpose: The aim of this study was to determine the prevalence of lower urinary tract symptoms (LUTS) and the factors influencing the healthcare-seeking behavior of men with LUTS. Materials and Methods: A cross-sectional survey was performed of 658 men selected using multi-staged sampling techniques. They were interviewed about LUTS and their healthcare-seeking behavior. The data were analysed using PASW Statistics ver. 18. Associations between specific factors and healthcare-seeking behavior were examined using the chi-square and Fisher exact tests. Results: The overall prevalence of LUTS was 59.1%. Storage symptoms (48.2%) were more prevalent than voiding (36.8%) or post-micturition (29.9%) symptoms. Approximately a quarter (25.5%) had a poor quality of life (QoL) score. The average duration of symptoms before seeking help was 3.4 years. Almost half (46.8%) of the men with LUTS had never sought help. Perceptions of LUTS as an inevitable part of ageing, subjective feelings of wellness, financial constraints, and fear of surgery were the most common reasons for not seeking help. The most common reasons for seeking help were to moderate-severe symptoms, impaired QoL, and fear of cancer. Severe LUTS, impaired QoL, and the concomitant presence of erectile dysfunction, dysuria, or haematuria were clinical factors that positively influenced healthcare-seeking behavior. Conclusions: In this population-based study, we found that the prevalence of LUTS was very high amongst adult males. However, only about half of these men sought medical attention. Their healthcare-seeking behavior was influenced by severity of symptoms, QoL scores, and socio-demographic factors such as educational status.